A Foreign Policy in Transition : Moscow's Retreat from Central America and the Carribbean, 1985-1992 - Adams, Jan S. (Book collections on Project MUSE., 1992)
During his years of leadership in the Soviet Union, Mikhail Gorbachev initiated revolutionary changes in that country's foreign and domestic policies. A Foreign Policy in Transition charts the changing Soviet policies toward Central America and the Caribbean during the Gorbachev years, examines the effects of these policies on individual countries, and looks to the role that Russia and the other Soviet-successor states will play in this region in the 1990s. Jan S. Adams analyzes the factors shaping Gorbachev's foreign policy in Central America by surveying Soviet political views.